Pengembangan Tari Rentak Bulean Tradisi ke Kreasi di Kecamatan Rengat Barat Kabupaten Indragiri Hulu Provinsi Riau - Febri Lestari Anggraini; Darmawati Darmawati (Jurnal Mahasiswa Kreatif, 2023)
This study aims to describe the Development of Rentak Bulean Dance Tradition into Creation in West Rengat District, Indragiri Hulu Regency, Riau Province. This research uses qualitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments in the form of stationery, cameras and flash drives. The data in this study used primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing data are data reduction, data presentation and data verification.. The results showed that the development of Rentak Bulean dance carried out by an artist named Wasnuri Marja was by coaching and training the people of West Rengat District to learn Rentak Bulean dance. The development of Rentak Bulean dance movements slightly adds additional motives to the movements. Meanwhile, the development of Rentak Bulean dance is disseminated through rehearsal and performance activities. Modify costumes by homogenizing in terms of color. Meanwhile, Rentak Bulean dance development efforts by disseminating it through performances. Dissemination with an appearance at the welcoming event of big people in West Rengat District, Indragiri Hulu Regency, Riau Province. After the development of Rentak Bulean Dance, people are aware of the interesting arts in West Rengat District, especially to young men and women who are increasingly interested in learning Rentak Bulean dance.